El uso de las tecnologías de la información y comunicación en el proceso de aprendizaje de la Matemática elemental en el Segundo Año de Educación Básica Unidad Educativa Marco Aurelio Subía Martínez. - Barreno Otáñez, Verónica Maribel (2021)
The objective of this project was to show the learning process of Elementary Mathematics through the use of ICT in students in the second year of general basic education at Unidad Educativa Marco Aurelio Subía Martínez - Batalla de Panupali in the school year 2020-2021, For this purpose, the relevant technological tools were selected, the characteristics that ICTs should have in the educational process were determined, an interactive guide was designed to enhance students' learning of mathematics, and it was applied to evidence the results. The quantitative methodological approach of applied modality, explanatory level, quasi-experimental design was used. The survey was applied to twenty-two teachers involved, which allowed us to know that they do not use freely available software games and are unaware of the Wordwall, Anchor and Jamboard tools, which limits innovation in their educative work. To measure the impact of the implementation of the proposal, a pre-test and post-test were conducted with 118 students, who obtained an average of 7.2 score out of 10 in the first test and 9.5 in the second, which indicates that the interactive guide supported the educational process and contributed to the mastery of the required learning in this area.